Mechanisms of glutathione-conjugate efflux from the brain into blood: Involvement of multiple transporters in the course. Issue 1 (January 2020) - Okamura, Toshimitsu; Okada, Maki; Kikuchi, Tatsuya; Wakizaka, Hidekatsu; Zhang, Ming-Rong
Accumulation of detrimental glutathione-conjugated metabolites in the brain potentially causes neurological disorders, and must therefore be exported from the brain. However, in vivo mechanisms of glutathione-conjugates efflux from the brain remain unknown. We investigated the involvement of transporters in glutathione-conjugates efflux using 6-bromo-7-[ 11 C]methylpurine ([ 11 C]1 ), which enters the brain and is converted into its glutathione conjugate, S -(7-[ 11 C]methylpurin-6-yl)glutathione ([ 11 C]2 ). In mice of control and knockout of P-glycoprotein/breast cancer resistance protein and multidrug resistance-associated protein 2 ([ Mrp2 ] −/− ), [ 11 C]2 formed in the brain was rapidly cleared, with no significant difference in efflux rate. In contrast, [ 11 C]2 formed in the brain of Mrp 1 −/− mice was slowly cleared, whereas [ 11 C]2 microinjected into the brain of control and Mrp1 −/− mice was 75% cleared within 60 min, with no significant difference in efflux rate. These suggest that Mrp1 contributes to [ 11 C]2 efflux across cell membranes, but not BBB. Efflux rate of [ 11 C]2 formed in the brain was significantly lower in Mrp4 −/− and organic anion transporter 3 ( Oat3 ) −/− mice compared with control mice. In conclusion, Mrp1, Oat3, and Mrp4 mediate [ 11 C]2 efflux from the brain. Mrp1 may contribute to [ 11 C]2 efflux from brain parenchymal cells, while extracellular [ 11 C]2 is likely cleared across the BBB, partly by Oat3 and Mrp4.